Clinical and genetic aspects of albinism - V.V. Kadyshev; S.A. Ryazhskaya; O.V. Khalanskaya; N.V. Zhurkova; R.A. Zinchenko (РМЖ "Клиническая офтальмология")
V.V. Kadyshev, S.A. Ryazhskaya, O.V. Khalanskaya, N.V. Zhurkova, R.A. Zinchenko Research Center for Medical Genetics, Moscow, Russian Federation Albinism is a clinically and genetically heterogeneous group of hereditary diseases whose pathogenesis is mediated by impaired synthesis of melanin which results in its partial or total loss. Reduced melatonin level clinically manifests as skin, hair, and ocular hypopigmentation. Ocular presentations include hypopigmentation/lack of pigmentation of eye fundus and iris, foveal hypoplasia, low vision, nystagmus and strabismus, photophobia, iris transillumination, and asymmetrical decussation of nerve fibers at the optic chiasm. However, albinism can be a part of more complex genetic syndromes, e.g., Hermansky-Pudlak syndrome or Chediak-Higashi syndrome. These disorders should be identified as early as possible to start therapy to prevent life-threatening conditions. Partial albinism with ocular, skin or hair hypopigmentation not associated with melanogenesis (e.g., Griscelli syndrome, Waardenburg syndrome, Aland Island eye disease, etc.) also occurs. Each case of albinism requir es an accurate molecular genetic diagnosis to provide a personalized treatment approach, predict life expectancy and health status, and plan pregnancy. Keywords: albinism, Hermansky-Pudlak syndrome, Chediak-Higashi syndrome, hypopigmentation, clinical polymorphism, genetic heterogeneity. For citation: Kadyshev V.V., Ryazhskaya S.A., Khalanskaya O.V. et al. Clinical and genetic aspects of albinism. Russian Journal of Clinical Ophthalmology. 2021;21(3):175–180 (in Russ.). DOI: 10.32364/2311-7729-2021-21-3-175-180.